Resilient Leadership: The Impact of a Servant Leader on the Resilience of their Followers. Issue 4 (November 2020) - Eliot, Jason L.
The Problem: Businesses and their leaders regularly face disruptive change, uncertain economic futures and the pressure of improving employee well-being. To not only withstand these crises but to rebound and even grow stronger, organizations must develop resilient leaders and a resilient workforce. Human resource development (HRD) professionals are responsible for resilience development within an organization and need to understand whether the development of servant leaders also increases leader and workforce resilience. The Solution: Leaders with a high level of resilience are able to respond in positive ways to crises their organizations may encounter and, by exhibiting that resilience and those positive responses, are able to increase the level of resilience of those around them. Servant leaders focus their efforts on meeting the psychological needs and health of their followers and are therefore well placed to positively impact subordinate resilience. This article explores the ability of servant leadership to positively impact and grow the resilient capacity of those impacted by the servant leader. It proposes that HRD professionals can increase the resilience capabilities of an organization through the development of servant leaders who also exhibit resilient behaviors. The Stakeholders: This article benefits organizations, leaders, employees, and HRD professionals as well as resilience and leadership scholars and practitioners.